Zinc and strontium based phosphate glass beads: a novel material for bone tissue engineering. (25th October 2017) - AlQaysi, Mustafa; Aldaadaa, Alaa; Mordan, Nicky; Shah, Rishma; Knowles, Jonathan C
Abstract: Degradable phosphate-based glasses that contain strontium, zinc and calcium were investigated to examine their function as an osteoconductive material. Glass beads of the general formula of (P2 O5 )–(Na2 O)–(TiO2 )–(CaO)–(SrO) or (ZnO) were prepared by a melt quench technique followed by milling and spheroidisation. After performing x-ray diffraction on all the samples for glass structure evaluation, glass bead size distribution was initially measured by a scanning electron microscope (SEM). Then, some of these samples were immersed in deionised water to evaluate both the surface changes and measure the ion release rate, whereas other samples of glass beads were incubated in culture media to determine pH changes. Furthermore, human osteoblast-like osteosarcoma cells MG63 and human mesenchymal stem cells were seeded on the glass beads to determine their cytocompatibility via applying CCK assay, ALP assay and Ca assay. SEM images and fluorescence images of confocal microscopy were performed for the cellular studies. While mass degradation and ion release results displayed a significant increase with zinc and strontium incorporation within time, pH results showed an initial increase in pH followed by a decrease. Cellular studies emphasised that all formulations enhanced cellular proliferation. Phosphate glass beads with zinc content 5 mol% and strontium content of 17.5 mol%, (ZnO5) and (SrO17.5) respectively displayed more promising results although they were insignificantly different from that of control ( p  > 0.05). This may suggest their applicability in hard tissue engineering.